Sustained Opening of the Blood-Brain Barrier with Progressive Accumulation of White Matter Hyperintensities Following Ischemic Stroke - Imama Naqvi; Emi Hitomi; Richard Leigh (Brain Sciences, 2019)
Objective: To report a patient in whom an acute ischemic stroke precipitated chronic blood-brain barrier (BBB) disruption and expansion of vascular white matter hyperintensities (WMH) into regions of normal appearing white matter (NAWM) during the following year. Background: WMH are a common finding in patients with vascular risk factors such as a history of stroke. The pathophysiology of WMH is not fully understood; however, there is growing evidence to suggest that the development of WMH may be preceded by the BBB disruption in the NAWM. Methods: We studied a patient enrolled in the National Institutes of Health Natural History of Stroke Study who was scanned with magnetic resonance imaging (MRI) after presenting to the emergency room with an acute stroke. After a treatment with IV tPA, she underwent further MRI scanning at 2 h, 24 h, 5 days, 30 days, 90 days, 6 months, and 1-year post stroke. BBB permeability images were generated from the perfusion weighted imaging (PWI) source images. MRIs from each time point were co-registered to track changes in BBB disruption and WMH over time. Results: An 84-year-old woman presented after acute onset right hemiparesis, right-sided numbness and aphasia with an initial NIHSS of 13. MRI showed diffusion restriction in the left frontal lobe and decreased blood flow on perfusion imaging. Fluid attenuated inversion recovery (FLAIR) imaging showed bilateral confluent WMH involving the deep white matter and periventricular regions. She was treated with IV tPA without complication and her NIHSS improved initially to 3 and ultimately to 0. Permeability maps identified multiple regions of chronic BBB disruption remote from the acute stroke, predominantly spanning the junction of WMH and NAWM. The severity of BBB disruption was greatest at 24 h after the stroke but persisted on subsequent MRI scans. Progression of WMH into NAWM over the year of observation was detected bilaterally but was most dramatic in the regions adjacent to the initial stroke. Conclusions: WMH-associated BBB disruption may be exacerbated by an acute stroke, even in the contralateral hemisphere, and can persist for months after the initial event. Transformation of NAWM to WMH may be evident in areas of BBB disruption within a year after the stroke. Further studies are needed to investigate the relationship between chronic BBB disruption and progressive WMH in patients with a history of cerebrovascular disease and the potential for acute stroke to trigger or exacerbate the process leading to the development of WMH.